Tree gum-based renewable materials: Sustainable applications in nanotechnology, biomedical and environmental fields - Padil, Vinod V. T. (Biotechnol Adv, 2018)
The prospective uses of tree gum polysaccharides and their nanostructures in various aspects of food, water, energy, biotechnology, environment and medicine industries, have garnered a great deal of attention recently. In addition to extensive applications of tree gums in food, there are substantial non-food applications of these commercial gums, which have gained widespread attention due to their availability, structural diversity and remarkable properties as ‘green’ bio-based renewable materials. Tree gums are obtainable as natural polysaccharides from various tree genera possessing exceptional properties, including their renewable, biocompatible, biodegradable, and non-toxic nature and their ability to undergo easy chemical modifications. This review focuses on non-food applications of several important commercially available gums (arabic, karaya, tragacanth, ghatti and kondagogu) for the greener synthesis and stabilization of metal/metal oxide NPs, production of electrospun fibers, environmental bioremediation, bio-catalysis, biosensors, coordination complexes of metal–hydrogels, and for antimicrobial and biomedical applications. Furthermore, polysaccharides acquired from botanical, seaweed, animal, and microbial origins are briefly compared with the characteristics of tree gum exudates.